2003
DOI: 10.1023/a:1025095927047
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study compared levels of emotional loneliness between sexual murderers and rapists who had not gone on to kill their victim/s. All participants were life-sentenced prisoners in the United Kingdom. Assessment consisted of a semistructured interview and was subjected to grounded theory analysis. This approach is defined as the breaking down, naming, comparing, and categorizing of data. As such, it is distinguished from other qualitative methods by the process of constant comparison. This continual sifting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…In order to assess the improvement in the fit of the MDS matrix these variables were removed which resulted in a more acceptable stress index of .13. However, emotional loneliness and low emphatic concern were considered important variables given the prevalence of the former among sexual killers and the association between sexual killing and psychopathy (of which empathy is a key element) highlighted in previous literature (Grubin, 1994;Kerr, Beech, & Murphy, 2013;Milsom et al, 2003). Therefore, a decision was made to reintroduce these measures in the final stage of the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the improvement in the fit of the MDS matrix these variables were removed which resulted in a more acceptable stress index of .13. However, emotional loneliness and low emphatic concern were considered important variables given the prevalence of the former among sexual killers and the association between sexual killing and psychopathy (of which empathy is a key element) highlighted in previous literature (Grubin, 1994;Kerr, Beech, & Murphy, 2013;Milsom et al, 2003). Therefore, a decision was made to reintroduce these measures in the final stage of the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Proulx and Sauvêtre (2007) also noted that sexual killers were more often diagnosed with sadism. Further, studies by Grubin (1994) and Milsom, Beech, and Webster (2003) found social and emotional loneliness to be significantly more prevalent in sexual killers, although Milsom et al (2003), while reporting significantly higher levels of social loneliness in adolescence, found little difference in terms of adult emotional loneliness. In line with these findings, Nicole and Proulx (2007) found significantly higher levels of peer isolation in adolescence, but the authors did not comment on levels of emotional loneliness in adulthood.…”
Section: Introductionmentioning
confidence: 90%
“…With some consistency across studies, pre-crime anger and social and emotional isolation appear to be significant in the lead up to offending for sexual killers differentially to sexual aggressors (Grubin, 1994;Milsom, Beech, & Webster, 2003). According to Grubin (1994), sexual killers may experience difficulty with appropriately expressing anger, which seems to be congruent with Chéné and Cusson's (2007) finding that anger in the lead up to the offense, but not during the attack, predicted killing as opposed to a non-fatal sexual assault.…”
mentioning
confidence: 99%
“…Langevin et al (1988) also found general lifestyle anger to be much more characteristic of sexual killers than sexual aggressors or non-sexual killers, although it should be noted that the sample of sexual aggressors in this study excluded cases where there had been physical violence. With regard to social and emotional isolation, impoverished peer relationships particularly during crucial developmental periods are commonly reported by sexual killers (Grubin, 1994; Milsom et al, 2003; Nicole & Proulx, 2007), with an emphasis on experiences suggesting rejection (perceived or actual) rather than internally attributed seclusion. This indicates that loneliness should be considered a possible precursor in the offense pathways of the perpetrators of this type of crime.…”
mentioning
confidence: 99%
“…Studies of predatory offenders have also revealed compelling inferences about their implicit motivations, including tacit beliefs about sexuality and gender (Beech et al, 2005; Beech et al, 2006; Meloy, 2002; Meloy & Gacono, 1992; Milsom et al, 2003). It is reasonable to suppose that factors only indirectly related to immediate self-perception and awareness of motivations play a role in violent reactions, even when this behavior is an acknowledged part of an individual’s personal identity.…”
Section: The Need For First Person Accountsmentioning
confidence: 99%